2005
DOI: 10.1007/s11173-005-0128-9
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Characterization of N,N-bis(2-{[(2,2-Dimethyl-1,3-Dioxolan-4-yl)Methyl]Amino}Ethyl) N′,N′-Dihydroxyethanediimidamide and Its Complexes

Abstract: 1 Transition metal complexes of vic -dioximes have been of particular interest as biological model compounds [1]. The high stability of the complexes prepared with dioxime ligands has been extensively used for various purposes including model compounds for vitamin B 12 or trace metal analysis [2]. Coordination compounds of vic -dioximes have been widely investigated as analytical reagents, models for biological systems, such as vitamin B 12 , compounds having columnar stacking thought to be a reason for their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The mononuclear complex of Ni(II) is diamagnetic, while Co(II) and Cu(II) are paramagnetic. According to the literature, square-planer geometry of the structure of the Ni(II), Co(II), and Cu(II) complexes may be reasonable [29,[31][32][33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mononuclear complex of Ni(II) is diamagnetic, while Co(II) and Cu(II) are paramagnetic. According to the literature, square-planer geometry of the structure of the Ni(II), Co(II), and Cu(II) complexes may be reasonable [29,[31][32][33].…”
Section: Resultsmentioning
confidence: 99%
“…The inflation of the t.g.a. curves of all the complexes at a temperature below 800 ∘ C indicates the decomposition of the fully organic part of the chelate, leaving the metallic oxide at the final temperature [33,35,36].…”
Section: Resultsmentioning
confidence: 99%
“…28,29 A weak broadband in 3421 cm -1 due to the OH group in the free Schiff base ligand was not observed in the infrared spectra of the nickel and vanadyl complexes which indicated that phenolic oxygen was deprotonated and coordinated in two complexes. 30 Additional support for the formation of the complexes were provided by the existence of weak intensity bands at around 504-691 cm -1 region which were attributed to the formation of M-N and M-O, respectively. These variations confirmed the coordination of nickel with the azomethine nitrogen and phenolic oxygen of the Schiff base.…”
Section: Ir Spectramentioning
confidence: 92%
“…The spectra exhibit the azomethine À C=N À carbon at 131.54 ppm. [18] The phenolic carbons appear in the range of 150.80 ppm. [18] The chemical shift of aromatic carbons appears in the range from 113.50 ppm to 131.09 ppm.…”
Section: C Nmr Spectramentioning
confidence: 99%